Биотопическое распределение наземных моллюсков города Львова и его окрестностей - Сверлова, Н.В. (Вестник зоологии, 2000)
Исследовано распределение наземных моллюсков по городским и пригородным биотопам Львова. Проанализированы изменения видового состава моллюсков при смене лесных биотопов парковыми. Проведен сравнительный анализ малакофаун Львова и других урбоэкосистем Восточной и Средней Европы. Отмечено богатство малакофауны Львова, наличие в ней некоторых не типичных для урбоэкосистем видов. The distribution of land molluscs among urban and suburban biotopes in Lviv has been investigated. The changes in species structure under the effect of substitution of the park biotopes for the forest ones have been analysed. Also the comparative analysis of molluscs faunas in Lviv and other urban ecosystems of Western and Middle Europe has been carried out. We mark the abundance of molluscs fauna in Lviv and the availability of some species unusial for urban ecosystems.